2016
DOI: 10.1051/0004-6361/201527269
|View full text |Cite
|
Sign up to set email alerts
|

Fossil groups in the Millennium simulation

Abstract: Aims. We investigate the evolution of bright and faint galaxies in fossil and non-fossil groups. Methods. We used mock galaxies constructed based on the Millennium run simulation II. We identified fossil groups at redshift zero according to two different selection criteria, and then built reliable control samples of non-fossil groups that reproduce the fossil virial mass and assembly time distributions. The faint galaxies were defined as having r-band absolute magnitudes in the range [−16, −11]. We analysed th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
2
12
0
1
Order By: Relevance
“…This is in line with the more recent last major merger and recent significant growth of the BGG due to merging we find for fossils, and as has been found in other theoretical studies as well (e.g. Díaz-Giménez et al 2008;Kanagusuku et al 2016).…”
Section: Observational Implicationssupporting
confidence: 93%
See 1 more Smart Citation
“…This is in line with the more recent last major merger and recent significant growth of the BGG due to merging we find for fossils, and as has been found in other theoretical studies as well (e.g. Díaz-Giménez et al 2008;Kanagusuku et al 2016).…”
Section: Observational Implicationssupporting
confidence: 93%
“…We also find support for the idea of a 'fossil phase' (von Benda-Beckmann et al 2008) whereby groups only temporarily exist with a large magnitude gap due to recent mergers of satellites with the central without recent infall of new satellites, in good agreement with previous studies of simulated fossils (von Benda-Beckmann et al 2008;Dariush et al 2010;Gozaliasl et al 2014;Kanagusuku et al 2016). As can be seen in our Fig.…”
Section: Group Mass Assembly Historysupporting
confidence: 92%
“…We found that 23.1 ± 2.5% of the CASSOWARY systems are Jones fossil progenitors and 28.9 ± 2.5% are Dariush fossil progenitors. This higher rate of fossil progenitors in the CASSOWARY sample is not surprising considering that Kanagusuku et al (2016) found that in the Millennium Simulation, systems which were fossils at z = 0 finished forming their BGG (creating the required ∆m 12 /∆m 14 r-band magnitude gap) between 0.3 < z < 0.6 on average. Since the average redshift of the CASSOWARY members is z ∼ 0.4, we expect to see a collection of nearfossil systems, as we are seeing analogs to today's fossil systems in mid-cannibalization of their L * members.…”
Section: Cassowary Strong Lensing Samplementioning
confidence: 70%
“…The apparent fossil deficit could be accounted for due to the redshift range of our sample (0.2 < z < 0.7). Since most fossils discovered lie near z ∼ 0.1, and Kanagusuku et al (2016) found in the Millennium Simulation that most z = 0 fossils made the transition between 0.3 < z < 0.6, there could be a lower fossil fraction in our samples.…”
Section: Non-lensing Control Samplementioning
confidence: 84%
“…Results from N-body simulations by von Benda-Beckmann et al (2008) supported the notion that not all fossils are old structures, as they found many instances of fossil systems being both formed and destroyed since z < 0.9 indicating this may be a phase of group evolution that all groups have a chance of passing into and out of. A later study by Kanagusuku et al (2016) found in the Millennium simulation that most groups which are classified as fossils at z = 0 assembled their BGGs between 0.3 < z < 0.6. These progenitors to today's fossils would be expected to exist near this redshift space and have imminent/ongoing major merging between intermediate mass galaxies and the BGG.…”
Section: Introductionmentioning
confidence: 95%